2018
DOI: 10.1038/s41598-018-22254-4
|View full text |Cite
|
Sign up to set email alerts
|

Computationally-Guided Development of a Stromal Inflammation Histologic Biomarker in Lung Squamous Cell Carcinoma

Abstract: The goal of this study is to use computational pathology to help guide the development of human-based prognostic H&E biomarker(s) suitable for research and potential clinical use in lung squamous cell carcinoma (SCC). We started with high-throughput computational image analysis with tissue microarrays (TMAs) to screen for histologic features associated with patient overall survival, and found that features related to stromal inflammation were the most strongly prognostic. Based on this, we developed an H&E str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…There is no established grading system for the extent of inflammation in the neoadjuvant setting on the basis of light microscopic review of hematoxylin and eosin (H&E) stained slides, although several approaches have been proposed in studies without neoadjuvant therapy. [75][76][77] Junker et al 30 described marked swelling of tumor cells after neoadjuvant therapy more often in adenocarcinomas than in squamous cell carcinomas. In rare cases, it may be difficult to differentiate single tumor cells or small clusters of tumor cells after neoadjuvant therapy from cells of a histiocytic reaction on the basis of H&E alone.…”
Section: Recommendation 4:mentioning
confidence: 99%
“…There is no established grading system for the extent of inflammation in the neoadjuvant setting on the basis of light microscopic review of hematoxylin and eosin (H&E) stained slides, although several approaches have been proposed in studies without neoadjuvant therapy. [75][76][77] Junker et al 30 described marked swelling of tumor cells after neoadjuvant therapy more often in adenocarcinomas than in squamous cell carcinomas. In rare cases, it may be difficult to differentiate single tumor cells or small clusters of tumor cells after neoadjuvant therapy from cells of a histiocytic reaction on the basis of H&E alone.…”
Section: Recommendation 4:mentioning
confidence: 99%
“…Wu et al [108] developed a U‐Net‐based end‐to‐end DL model to automatically detect tumors, segment cells, and calculate the TPS of PD‐L1 by highlighting PD‐L1‐positive tumor cells. In a study with 437 NSCLC patients, Xia et al [109] demonstrated the utility of computational pathology approaches in the discovery of newer biomarkers. Using tissue microarrays, they discovered a new histologic feature, the stroma inflammation score, which was highly correlated with patient overall survival in NSCLC.…”
Section: Ai Applications In Lung Pathologymentioning
confidence: 99%
“…The potential benefits are more repeatable cell counting and measurement, and saving pathologists time in their everyday work routine [ 27 ]. Additionally, by measuring many cell and inter-cell parameters, AI can potentially help find new HE phenomena that can later be used [ 140 , 141 , 142 ]. Some commercially available software is made for breast cancers and scoring ER, PGR, Ki67, and HER-2.…”
Section: Digital Imaging In Quantitative Pathological Assessmentmentioning
confidence: 99%